The Natural Compound Homoharringtonine Presents Broad Antiviral Activity In Vitro and In Vivo - Dong, Hui-Jun; Wang, Zhao-Hua; Meng, Wen; Li, Cui-Cui; Hu, Yan-Xin; Zhou, Lei; Wang, Xiao-Jia (Viruses, 2018)
To complement traditional antivirals, natural compounds that act via host targets and present high barriers to resistance are of increasing interest. In the work reported here, we detected that homoharringtonine (HHT) presents effective antiviral activity. HHT completely inhibited infections of vesicular stomatitis virus (VSV), Newcastle disease virus (NDV), and porcine epidemic diarrhea virus (PEDV) at concentrations of 50, 100, and 500 nM in cell cultures, respectively. Treatment with HHT at doses of 0.05 or 0.2 mg/kg significantly reduced viral load and relieved severe symptoms in PEDV- or NDV-infected animals. HHT treatment, however, moderately inhibited avian influenza virus (AIV) infection, suggesting its potent antiviral action is restricted to a number of classes of RNA viruses. In this study, we also observed that HHT actively inhibited herpes simplex virus type 1 (HSV-1) replication with a 50% inhibitory concentration (IC50) of 139 nM; the treatment with HHT at 1000 nM led to reductions of three orders of magnitude. Moreover, HHT antagonized the phosphorylation level of endogenous and exogenous eukaryotic initiation factor 4E (p-eIF4E), which might regulate the selective translation of specific messenger RNA (mRNA). HHT provides a starting point for further progress toward the clinical development of broad-spectrum antivirals.